Adaptive immune response in pathogenesis and treatment of head and neck squamous cell carcinoma: the influence of immunosuppression factors and gender - A. I. Stukan; R. A. Murashko; N. A. Tsygan; A. Yu. Goryainova; O. N. Nefedov; V. A. Porkhanov (Опухоли головы и шеи, 2022)
An obvious trend of the last decade in head and neck squamous cell carcinoma pathogenesis evaluation is awareness of the impact of immune response disorders on disease manifestation. The review presents an analysis of the differences in the type and degree of immunosuppression, as well as treatment response in head and neck squamous cell carcinoma patients in accordance with influencing carcinogenic factor, gender, age of the patient and concomitant diseases. An increase in CD8+ T-lymphocytes and a decrease of memory T-cells has been evaluated in smoking and alcohol abusing patients with head and neck squamous cell carcinoma, and a smaller number of CD8+ T-lymphocytes were detected in the tumor microenvironment compared to non-smoking and non-drinking patients. Studies have shown that the improved prognosis of patients with human papillomavirus (Hpv) – associated head and neck squamous cell carcinoma is largely due to the presence of antibodies against Hpv E6 and E7, E7-specific CD8+T lymphocytes in periphe ral blood and a high level of tumor-infiltrating T lymphocytes. The issue of gender differences in the type of immune response is widely discussed. It has been shown that the use of immune response checkpoint inhibitors is more effective in improving survival rates in men, and the use of these drugs in combination with chemotherapy is more effective in women. In addition, in elderly cancer patients, numerous age-associated T-lymphocyte’s function changes were revealed, including a decrease in the number of naive T-lymphocytes due to age-related involution of the thymus and an in crease in the relative number of memory cells and effector cells. Thus, it is clear that immunosuppression type, as well as treatment response, differ depending on the influencing factor, gender, age of the patient, as well as comorbidities.